A national investigation of the correlation between perceptions of human resources management practices and organizational effectiveness - A. J. Templer; K. B. Hofmeyr (South African Journal of Business Management, 1989)
This study investigates the extent to which organization effectiveness can be predicted from human resources management (HRM) practices. The results are based on data gathered from attitude surveys of a large sample of employees in 38 companies across the USA. It is found that HRM practices can be summarized in six HRM dimensions which predict organization effectiveness at the departmental level, as perceived by employees. Such effectiveness appears to be linked to HRM practices which stress communication, job clarity, management concern, and equity. Opportunities for future research are suggested and implications for management practice are presented.
Keywords: 650